The Effects of Perceived Brand Localness to Brand Trustworthiness - Noronen, Siru (My University, 2025)
Globalization has changed the way businesses operate, offering new opportunities for growth but also creating new challenges for brand management. While global brands aim for uniformity, markets that are increasingly demanding on localization to meet consumer preferences is leading companies to adopt “glocal” strategies, where global brands take the local consumers’ preferences and culture into account. This thesis aims to examine how perceived brand localness (PBL) affects brand trustworthiness and how PBL is created through brand localization strategies. Drawing from existing literature, the study explores how perceived brand localness is created through cultural adaptation of brand communication, language, visual identity, humor and offerings. This thesis then defines brand trustworthiness as multi-dimensional concept including competence and expertise, integrity and consistency, benevolence, shared values and communication. Finally, the relationship between the two is analyzed through signaling theory, social identity theory and ethnocentric mindset theory. Findings indicate that brands perceived as local are more likely to been seen as competent, benevolent, value-aligned and communicatively transparent, thereby enhancing consumers’ perception of trustworthiness. This thesis contributes to the literature by providing a conceptual framework for brand trustworthiness, distinguishing it from brand trust and demonstrating how PBL influences consumers’ trust perceptions. This study provides practical insights for brand managers seeking to implement localization strategies to strengthen brand trustworthiness among consumers.

Globalisaatio on muuttanut tavan, jolla yritykset toimivat, tarjoten uusia kasvumahdollisuuksia, mutta myös luoden uusia haasteita brändien hallintaan. Globaalit brändit pyrkivät yhtenäisyyteen. Kuitenkin markkinoiden kasvavan vaatimuksen vuoksi, on yrityksien omaksuttava “glokalisaatiostrategioita”, jossa globaalisti toimivien brändien tulee ottaa paikallisten kuluttajien toiveet ja kulttuuri huomioon. Tämä tutkielma pyrkii selvittämään, miten koettu brändin paikallisuus vaikuttaa brändin luotettavuuteen ja miten koettu paikallisuus syntyy brändin lokalisaatiostrategioiden kautta. Aiemman tutkimuskirjallisuuden pohjalta tutkielma tarkastelee, miten koettu brändin paikallisuus syntyy brändiviestinnän, kielen, visuaalisen identiteetin, huumorin ja tarjonnan kulttuurisen mukauttamisen kautta. Tutkielmassa myös määritellään brändin luotettavuus moniulotteiseksi käsitteeksi, johon sisältyvät osaaminen ja asiantuntijuus, eheys ja johdonmukaisuus, hyväntahtoisuus, jaetut arvot sekä viestintä. Näiden välistä suhdetta analysoidaan signaaliteorian, sosiaalisen identiteetin teorian ja etnosentrisen ajattelutavan teorian avulla. Tulokset osoittavat, että paikallisina koetut brändit nähdään todennäköisemmin osaavina, hyväntahtoisina, arvoiltaan yhdenmukaisina ja viestinnältään avoimina, mikä vahvistaa kuluttajien käsitystä luotettavuudesta. Tämä tutkielma tuo lisäarvoa kirjallisuuteen tarjoamalla käsitteellisen viitekehyksen brändin luotettavuudelle, erottaen sen brändiluottamuksesta ja osoittaen, miten koettu paikallisuus vaikuttaa kuluttajien luottamuksen muodostumiseen. Tutkimus tarjoaa käytännön näkökulmia brändijohtajille, jotka haluavat toteuttaa lokalisaatiostrategioita brändin luotettavuuden vahvistamiseksi kuluttajien keskuudessa.
Keywords: Perceived Brand Localness (PBL), Brand Trustworthiness, Brand Localization, Global Branding, Consumer Trust, Cultural Adaptation, Brand Communication, Brändin koettu paikallisuus, Brändin luotettavuus, Brändin lokalisaatio, Kuluttajien luottamus, Kulttuurinen mukautuminen, Brändiviestintä